Predictors of oxygen uptake and performance during tennis - Cooke, K.; Davey, P. (International Journal of Sports Medicine, 2008)
Tennis ball machine tests permit the concurrent measurement of physiological function and groundstroke performance in a sport specific manner. The purpose of this study was to understand further the demands of groundstroke performance during a test with progressively increasing ball frequency, by determining the running speed between strokes, upper and lower limb acceleration and pulmonary gas exchange throughout. Sixteen tennis players (n = 8, male; n = 8, female; all right handed) completed three 4 min stages of hitting against a ball feed frequency of 15, 20, 25 ball · min-1 interspersed by 8 min of rest. Stepwise multiple regression analysis identified a predictive model of V·O2 containing the variables of left arm acceleration and right ankle acceleration but not running speed (p < 0.0001; adjusted r2 = 0.93; left wrist acceleration Beta = 1.04; right ankle acceleration Beta = - 0.12; S. E. E. = 2.61 ml · kg-1 · min-1). Regression analysis found that the strongest predictors of stroke performance (ball speed [m · s-1] × stroke accuracy [%]) were right wrist acceleration and stroke economy (p < 0.0001; adjusted r2 = 0.28; right wrist acceleration Beta = - 0.59; movement economy Beta = - 0.28). The findings of this study highlight the contribution of limb acceleration and not running speed to the oxygen cost of tennis groundstroke performance.